Cyclopalladated compounds containing 2,6-lutidine: Synthesis, spectral and biological studies - da Cunha, Gislaine A. [UNESP]; de Souza, Ronan F.F. [UNESP]; de Farias, Renan L. [UNESP]; Moreira, Mariete B. [UNESP]; Silva, Débora E.S. [UNESP]; Zanetti, Renan D. [UNESP]; Garcia, Daniel M.; Spindola, Daniel G.; Michelin, Luis F.G.; Bincoletto, Claudia; de Souza, Aline A.; Antunes, Alyne A.; et al. (Elsevier, 2020)
Bridge splitting reactions between [Pd(C2,N-dmba)(μ-X)]2 (dmba = N,N-dimethylbenzylamine; X = Cl, I, N3, NCO) and 2,6-lutidine (lut) in the 1:2 molar ratio at room temperature afforded cyclopalladated compounds of general formulae [Pd(C2,N-dmba)(X)(lut)] {X = Cl− (1), I−(2), NNN−(3), NCO−(4)}, which were characterized by elemental analyses and infrared (IR), 1H NMR spectroscopy. The molecular structures of all synthesized palladacycles have been solved by single-crystal X-ray crystallography. The cytotoxicity of the cyclopalladated compounds has been evaluated against a panel of murine {mammary carcinoma (4T1) and melanoma (B16F10-Nex2)} and human {melanoma (A2058, SK-MEL-110 and SK-MEL-5) tumor cell lines. All complexes were about 10 to 100-fold more active than cisplatin, depending on the tested tumor cell line. For comparison purposes, the cytotoxic effects of 1–4 towards human lung fibroblasts (MRC-5) have also been tested. The late apoptosis-inducing properties of 1–4 compounds in SK-MEL-5 cells were verified 24 h incubation using annexin V-Fluorescein isothiocyanate (FITC)/propidium iodide (PI). The binding properties of the model compound 1 on human serum albumin (HSA) and calf thymus DNA (ct-DNA) have been studied using circular dichroism and fluorescence spectroscopy. Docking simulations have been carried out to gain more information about the interaction of the palladacycle and HSA. The ability of compounds 1–4 to inhibit the activity of cathepsin B and L has also been investigated in this work.
Keywords: 2,6-Lutidine; Cathepsins; Cell death; Cyclopalladated complex; Cytotoxicity; DNA